Integrated methane capture system with isometric pipeline network in the refuse derived fuel plant - Puspito Sari, Deffi Ayu; Irawan, Diki S.; Nasython, Kun; Karyapraja, Humam A.; Fadiilah, Dessy (Journal of Water and Land Development, 2026)
Landfills remain one of the largest anthropogenic sources of methane (CH4), a potent greenhouse gas with significant climate impact. Effective capture and utilisation of landfill gas are therefore essential to reduce emissions while supporting renewable energy recovery. This study presents the integrated design of a methane gas capture system with an isometric pipeline network in the Jeruklegi refuse derived fuel (RDF) plant, Cilacap. The research aimed to optimise methane recovery through technical evaluation of pipeline configuration, head loss calculations, and compressor specifications. The methodology included estimating methane generation potential using the landfill gas emissions model (LandGEM) and Intergovernmental Panel on Climate Change (IPCC) guidelines, calculating major and minor head losses in a 160 mm pipeline system, and determining blower requirements. The potential methane production was estimated at approximately 2.78∙106 m3∙y−1, while the designed collection system could capture around 2.06∙106 m3∙y−1. This corresponds to a capture efficiency of nearly 75%, which aligns with international benchmarks for modern landfill gas systems (60−85%). The required blower capacity was determined to be ≥320 m3∙h−1 at a vacuum pressure of from −10,000 to −20,000 Pa, with an optimal power range of 1−2.2 kW, indicating that larger units (4–5 kW) would be oversized and inefficient. The findings highlight the feasibility of applying an integrated gas capture system in RDF plants to mitigate greenhouse gas emissions while ensuring energy recovery. This work provides a practical engineering reference for sustainable landfill gas management and supports the transition toward low-carbon waste treatment technologies.